2020
DOI: 10.1094/pdis-11-19-2302-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of New Zealand Provenance Leptospermum scoparium, Kunzea robusta, Kunzea linearis, and Metrosideros excelsa to Austropuccinia psidii

Abstract: Resistance to the pandemic strain of Austropuccinia psidii was identified in New Zealand provenance Leptospermum scoparium, Kunzea robusta, and K. linearis plants. Only 1 Metrosideros excelsa-resistant plant was found (of the 570 tested) and no resistant plants of either Lophomyrtus bullata or L. obcordata were found. Three types of resistance were identified in Leptospermum scoparium. The first two, a putative immune response and a hypersensitive response, are leaf resistance mechanisms found in other myrtace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Despite a number of plants being surveyed until May 2018, only one plant was found to be infected in nature. Artifical inoculation studies have, however, shown that the species is susceptible (Smith et al 2020) which suggests that physiological or environmental factors in the field may be limiting the myrtle rust infections in mānuka plantations, as reported for other Myrtaceae hosts in Australia (Makinson 2018).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Despite a number of plants being surveyed until May 2018, only one plant was found to be infected in nature. Artifical inoculation studies have, however, shown that the species is susceptible (Smith et al 2020) which suggests that physiological or environmental factors in the field may be limiting the myrtle rust infections in mānuka plantations, as reported for other Myrtaceae hosts in Australia (Makinson 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Infection and expression of disease symptoms requires the combination of pathogen, susceptible host and conducive environment, and the absence of detection may be due to the lack of inoculum exposure or suitable environmental conditions. Resistance screening on Kunzea robusta has shown that this species is susceptible to A. psidii although the population tested did have more resistance than some of the other New Zealand Myrtaceae species in which genetic resistance was either low or non-existent (Smith et al 2020). Lophomyrtus bullata and hybrids with L. obcordata were the most frequently detected infected plant species and both resistance screening and Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Artificial inoculation of Lophomyrtus spp. with A. psidii has also shown the species is highly susceptible and thus far, there is no indication of any resistance in this species (Smith et al 2020). This highlights the need to focus on conservation and germplasm storage of Lophomyrtus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Nothing is known about the genetic resistance of L. scoparium or Metrosideros spp. in the two sites monitored, although artificial testing of L. scoparium against A. psidii has shown this species is susceptible and there are multiple forms of resistance in the population (Smith et al 2020). During the incursion response there was a high number of myrtle rust detections on Metrosideros spp., but the majority of these detections were on Metrosideros excelsa and hybrids, and not on species of climbing rātā (Beresford et al 2019;Toome-Heller et al 2020).…”
Section: Discussionmentioning
confidence: 99%